Hemodynamic effects of pneumonia: I. Normal and hypodynamic responses - Benson, Herbert; Akbarian, Mohammed; Adler, Lawrence N.; Abelmann, Walter H. (The Journal of Clinical Investigation, 1970)
Since an excessive mortality from pneumonia persists in spite of antimicrobial therapy, the hemodynamics during and after the acute phase of pneumonia were studied in 17 patients. None of the patients had clinical heart disease and all had normal venous pressures. The arteriovenous oxygen difference was used to assess the adequacy of the circulation to meet peripheral tissue perfusion, and a spectrum of arteriovenous oxygen differences was noted. In 11 patients, tissue perfusion was considered adequate because the arteriovenous oxygen difference did not exceed 5.5 vol%. In six patients, the arteriovenous oxygen difference was greater than 5.5 vol% and these six patients differed hemodynamically from the others. In these six patients during the acute phase of pneumonia, cardiac output was decreased, and total peripheral resistance and hematocrit were increased. When five patients with varying arteriovenous oxygen difference were studied during exercise in the acute phase, cardiac output increased while venous pressure remained unchanged. Arteriovenous oxygen difference in these five exercising patients increased in all, but most markedly in those with an initially widened arteriovenous oxygen difference. The inadequate response to pneumonia is most consistent with depressed myocardial function, but the possibility of decreased intravascular volume as a contributory factor could not be excluded.